Corporate finance : theory and practice - Pierre Vernimmen (John Wiley & Sons, 2024)
This book offers: A balanced blend of theory and practice: authors hold academic positions at top ranking universities and business schools and are also investment bankers, private investors or sit on the boards of listed and unlisted companies A presentation of concepts that explain situations, followed by a discussion of techniques in a direct and succinct style Content enriched by the www.vernimmen.com website, which with 1,500 daily visitors is one of the leading finance teaching sites worldwide